Antitumor effect of dendritic cell loaded ex vivo and in vivo with tumor-associated antigens in lung cancer model. (July 2014) - Son, Cheol-Hun; Bae, Jae-Ho; Shin, Dong-Yeok; Lee, Hong-Rae; Yang, Kwangmo; Park, You-Soo
<x xml:space="preserve">Abstract</x> Various ex vivo or in vivo loading protocols have been developed or evaluated for the delivery of tumor antigens to dendritic cells (DCs). We compared the antitumor effect of mature DCs electroporation-pulsed (EP/mDC) ex vivo with tumor cell lysate and immature DCs (iDCs) injected into the tumor apoptosed by ionizing radiation (IR/iDC) in lung cancer model. DCs were generated from bone marrow of C57BL/6 mice. Ionizing radiation (IR) was applied at a dose of 10 Gy to the tumor on the right thigh. iDCs were intratumorally injected into the irradiated tumor and EP/mDC was injected subcutaneously in the right flank. DC injection induced strong tumor-specific immunity against Lewis lung carcinoma, as compared with the tumor-bearing control and IR only treated mice. The growth of a distant tumor on the right and left flank was inhibited by IR/iDC and EP/mDC. Particularly, IR/iDC resulted in a more significant inhibition of tumor growth and prolonged survival time. It was related to increase of tumor-specific interferon-gamma, cytotoxicity, and decrease of regulatory T-cells. The results indicate that DCs electroporation-pulsed with tumor cell lysate induce a potent antitumor effect, but that iDCs intratumoral injected into the irradiated tumor induce a more potent antitumor effect.